Bacteremia and conventional diagnosis of Sphingobacterium spiritivorum. A case report - Elio Jesús Núñez Tamayo; Susana Chamero Melgarejo; Rafael Gómez Marrero; Nancy Ramírez Martínez; Eva María García Mauri; Remberto González Enoa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2003)
This is a case report of septicaemia due to Sphingobacterium Spiritovirum that caused acute symmetric acronecrosis in a previously healthy man who received medical assistance at the University Hospital ¨Dr. Gustavo Aldereguía Lima¨ from Cienfuegos province in November 2002. The clinical symptoms were: fever, lumbar pain and chills which evolved to shock with general malaise, accompanied with paresthesia, symptoms of distal necrosis in the four members, nose and ear. Sphingobacterium Spiritovirum was diagnosed by the conventional diagnosis of growing in the marrow tests and serial blood cultures. Susceptibility antimicrobial tests were sensible to sulphametoxazole - trimetropin and resistant to tetracycline, aztreonam, ceftriaxone and imipenem. The bibliography consulted did not evidence any previous isolation in Cuba .